2008
DOI: 10.1177/0278364907088401
|View full text |Cite
|
Sign up to set email alerts
|

Learning to Move in Modular Robots using Central Pattern Generators and Online Optimization

Abstract: This article addresses the problem of how modular robotics systems, i.e. systems composed of multiple modules that can be configured into different robotic structures, can learn to locomote. In particular, we tackle the problems of online learning, that is, learning while moving, and the problem of dealing with unknown arbitrary robotic structures.We propose a framework for learning locomotion controllers based on two components: a central pattern generator (CPG) and a gradient-free optimization algorithm: Pow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
93
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(93 citation statements)
references
References 45 publications
0
93
0
Order By: Relevance
“…Based on biomimetic central pattern generators and on information from distributed distance sensors, neuromuscular motion control for an undulatory robot models was presented (Sfakiotakis and Tsakiris 2008). By implementing the CPG as a system of coupled nonlinear oscillators in the modular robotic system, Sproewitz ad-dressed the problem of learning to locomote in modular robotic systems which composed of multiple modules that can be configured into different robotic structures (Sproewitz et al 2008).…”
mentioning
confidence: 99%
“…Based on biomimetic central pattern generators and on information from distributed distance sensors, neuromuscular motion control for an undulatory robot models was presented (Sfakiotakis and Tsakiris 2008). By implementing the CPG as a system of coupled nonlinear oscillators in the modular robotic system, Sproewitz ad-dressed the problem of learning to locomote in modular robotic systems which composed of multiple modules that can be configured into different robotic structures (Sproewitz et al 2008).…”
mentioning
confidence: 99%
“…Parameters were manually extracted from the modular robot by exploiting symmetries. Follow-up work by Spröwitz et al demonstrated online optimization of 6 parameters on a physical robot in roughly 25-40 minutes [21]. We also try to realize simple, robust, fast, model-free, life-long learning on a modular robot.…”
Section: Related Workmentioning
confidence: 99%
“…Most robots learn their behaviors by tuning controllers [27], and some of them can adapt to unexpected situations [24]. The work in [28] used central-pattern-generator-based strategy to find efficient locomotion gaits after failures of several actuators.…”
Section: Resilient Robotsmentioning
confidence: 99%